Echoes of Olympus: Studies in the Reception of the Homeric Hymns in Hellenistic Poetry - Lam, Tsit Sze Jeremy (Trinity College Dublin. School of Histories & Humanities. Discipline of Classics, 2026)
In this thesis I investigate the Hellenistic poets' creative reception of the Homeric Hymns, a group of 33 poems attributed to Homer which address individual deities. My methodology focuses on unpacking the systematic intertextual relationship between one particular Homeric Hymn and one Hellenistic poem (or a series of related episodes in the longer Argonautica). The thesis consists of three chapters, arranged in a progressive order of the stages of human life which are central to each: infancy, childhood, and old age. Chapter 1, "From Infancy to Immortality," investigates Theocritus' Idyll 24 and its relationship with the Homeric Hymn to Demeter. I argue that the central eschatological concerns of this hymn, manifest in the failed immortalisation of a human baby followed by Demeter's establishment of the Eleusinian Mysteries, provide a foundation for conceptualising Heracles' ultimate apotheosis. Chapter 2, "Child Gods," reads Callimachus' Hymn to Artemis alongside the Homeric Hymn to Hermes, and investigates the phenomenon of child gods seeking to make their mark through the use of cunning and persuasion incongruent with their age. The exploits of Artemis and Hermes are moreover driven by a comparable sibling rivalry with Apollo, a dynamic that is reflected metapoetically in the intertextual programme of the two poems. Chapter 3, "Old Age and Prophecy," examines a series of interrelated episodes in Apollonius' Argonautica, beginning with the Argonauts' encounter with the aged prophet Phineus. Just as Phineus inherits his prophetic skill from Apollo, so this episode is indebted to the elaborate account of Apollo's Delphic oracle in the Homeric Hymn to Apollo, but with a significant twist that questions the benefits of Apollo's oracular communications. I also consider the influence of the hymn on Apollo's two Argonautic epiphanies at Thynias and Anaphe. The hymn therefore performs a structural function in binding these various Apolline episodes together.
APPROVED
Keywords: Hellenistic Poetry; Theocritus; Callimachus; Homeric Hymns; Apollonius; Reception; Intertextuality